Produktivitas Dan Komposisi Jenis Hasil Tangkapan Bagan Apung Berdasarkan Fase Bulan Di Perairan Sampolawa Kabupaten Buton Selatan - Lusi Dwi Apriliani; Abdullah Abdullah; Hasnia Arami; Naslina Alimina; Ahmad Mustafa (Universitas Halu Oleo, 2022)
Floating net is a fishing gear that is classified into the lift nets group. In addition to the light power factor, the moon phase factor is believed to affect the fish's response. The purpose of this study was to determine the effect of the phases of the moon on catches and the productivity of floating nets, as well as ti determine the composition of the species of fish caught according to the phases of the moon. This research was conducted from May to June 2022 in Sampolawa waters, South Buton. This study used a survey method on the catches of the floating lift nets during 27 trips. Observations were made on the first light, early dark, and dark moon phases. The results of the study found that the total catch in the early bright moon phase was 2,659 individuals, the early dark moon phase was 2,312 individuals and the dark moon phase was 694 individuals. There were 14 species of fish caught in all phases of the month of observation, where three (3) species of fish were dominant in each phase of the month, namely anchovies (Stolephorus sp), then bigeye scad (Selar crumenophthalmus) and sardine (Sardinella Sp). The moon phase has a significant effect on the number of individuals caught, whereas the early bright moon phase is the moon phase that has the highest productivity (5.5 kg/trip).